Land suitability assessment and self-sufficiency evaluation for fodder crop production in a hyper arid environment coupling GIS-based multi-criteria decision making and optimization - Hazrat Bilal (7367477) (2025)
Site selection for outdoor agricultural activities is crucial in hyper-arid environments. This study evaluates land suitability for fodder crop production in the State of Qatar. It aims to provide a multi-criteria evaluation based spatial decision support system, considering the usage of rainfall, treated wastewater, and groundwater for irrigation. Analytic Hierarchy Process and GIS-based multi-criteria approaches are used to calculate the weights of evaluation criteria and generate suitability maps. A considerable land area can potentially be used for fodder crop production, considering different water sources including groundwater, treated wastewater and rainfed irrigation. Results demonstrate that relying solely on rainfall limits the most suitable area for green fodder cultivation to just 8-653 km2. However, when groundwater and treated wastewater are incorporated into the water budget allocated for fodder production, the most suitable area expands to 25-2072 km2. An optimization model is then developed to estimate the maximum self-sufficiency that can be achieved between 2024 and 2030 considering land suitability maps and different water budgets. Some of the dominant limiting factors for fodder crop self-sufficiency are erratic rainfall, spatial heterogeneity in groundwater quality and transportation of wastewater for irrigation. To achieve self-sufficiency in fodder crop production, 456 km2 of land, 91.3 thousand cubic meter of water and 73–456 MWh of energy are required annually. Given the country's water budget and irrigation practices, the maximum self-sufficiency that can be achieved in 2030 is 48.6%, which entails the use of 57 million m3 of groundwater resources and up to 464 million m3 of treated sewage effluent. This highlights that, through strategic planning and sustainable water resource management, the country has the potential to significantly enhance its self-sufficiency in fodder crop production. Other Information Published in: Ecological Modelling License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ecolmodel.2025.111021